2021
DOI: 10.1371/journal.pone.0254685
|View full text |Cite
|
Sign up to set email alerts
|

The role of customer experience in the effect of online flow state on customer loyalty

Abstract: Purpose The Internet revolution has radically changed the means of conducting business all over the world in the past few decades. The digital medium enables consumers worldwide to shop online through B2C e-commerce websites in a convenient manner. Online websites compete to provide a compelling and seamless brand experience to retain their customers. In order to achieve this, fostering a state of flow may help the brands increase customer experience, customer satisfaction and loyalty. In this study, the afore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
3
20
1
10
Order By: Relevance
“…Based on these findings, it can be concluded that an online customer experience, which is a one-time event, directly impacts a long-term phenomenon like customer loyalty. However, because a better online flow state leads to a better overall brand experience, it aids in the development of stronger client loyalty ( Ertemel et al, 2021 ). The findings show that investing in a flawless online experience that puts customers in the flow keeps them amused and improves brand loyalty over experience.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it can be concluded that an online customer experience, which is a one-time event, directly impacts a long-term phenomenon like customer loyalty. However, because a better online flow state leads to a better overall brand experience, it aids in the development of stronger client loyalty ( Ertemel et al, 2021 ). The findings show that investing in a flawless online experience that puts customers in the flow keeps them amused and improves brand loyalty over experience.…”
Section: Discussionmentioning
confidence: 99%
“…Brand Experience has a positive and significant effect on consumer loyalty (Japutra, et al, 2021). Research from (Pratiwi, RS, et al, 2021;Ertemel, et al, 2021) also shows that brand experience affects brand loyalty. Thus the following hypothesis is proposed.…”
Section: Brand Experience On Brand Loyaltymentioning
confidence: 95%
“…The experience that consumers have of a product is brand experience. A good brand experience has a positive and significant impact on consumer loyalty (Ertemel et al, 2021). Brand Experience has a positive and significant effect on consumer loyalty (Japutra, et al, 2021).…”
Section: Brand Experience On Brand Loyaltymentioning
confidence: 99%
“…Thus, it demonstrates that few research studies with a narrow scope have been undertaken in Asia. In contrast, brand loyalty among consumers is a serious issue in the present era ( Safeer et al, 2021c ), and several researchers advocate for additional research on consumer brand loyalty by examining firms’ innovation activities through the lens of consumer perceptions ( Zameer et al, 2019 ; Ertemel et al, 2021 ; Safeer et al, 2021c ). As a result, this research proposes that “how consumers perceive firms’ innovation activities affect their brand loyalty via brand prototypes, preferences, and recommendations?” Therefore, this study pursues the following specific aims in the context of Asia, including China, Pakistan, and Indonesia:…”
Section: Introductionmentioning
confidence: 99%